2002
DOI: 10.1101/gad.986602
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis by homologous recombination inD. melanogaster

Abstract: We used a recently developed method to produce mutant alleles of five endogenous Drosophila genes, including the homolog of the p53 tumor suppressor. Transgenic expression of the FLP site-specific recombinase and the I-SceI endonuclease generates extrachromosomal linear DNA molecules in vivo. These molecules undergo homologous recombination with the corresponding chromosomal locus to generate targeted alterations of the host genome. The results address several questions about the general utility of this techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
345
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(357 citation statements)
references
References 47 publications
11
345
0
1
Order By: Relevance
“…We produced DDNp53 or Dp53 in p53-null flies. 35 First, we found that elevated levels of Dp53 or DDNp53 led to robust caspase activation, indicating that each isoform can induce apoptosis in the absence of the endogenous p53 gene (Figures 5a and b). Next, we observed that DDNp53 retained the ability to increase wg expression in the p53-null flies (Figures 5d and d 0 ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We produced DDNp53 or Dp53 in p53-null flies. 35 First, we found that elevated levels of Dp53 or DDNp53 led to robust caspase activation, indicating that each isoform can induce apoptosis in the absence of the endogenous p53 gene (Figures 5a and b). Next, we observed that DDNp53 retained the ability to increase wg expression in the p53-null flies (Figures 5d and d 0 ).…”
Section: Resultsmentioning
confidence: 82%
“…The following transgenic and mutant fly stocks were used: MS1096-Gal4, en-Gal4, uas-lacZ and uas-RFP (Bloomington stock); uas-GFP, 43 rpr XRE -lacZ (rprZ) and dronc I29 (kind gifts from A Bergmann 25 ); p53R-GFPnls (p53 RE; a generous gift from J Abrams 15 ), rpr87, 44 deficiency (3L)H99 (Df(3L)H99, referred to as H99 45 ), PCNA-EmGFP 33 and p53-null (p53 [5A-1-4]). 35 The following genetic combinations were used to express transgenes in wing imaginal discs: (1) MS1096-Gal4,uas-GFP (MS10964GFP), (2) MS1096-Gal4;uas-Dp53 (MS10964Dp53), (3) MS1096-Gal4;uas-DDNp53 (MS10964 DDNp53), (4) enGal4/uas-Dp53 (en4Dp53), and (5) en-Gal4/uas-DDNp53 (en4DDNp53). Flies were raised under standard conditions at 25 1C.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 These findings were further supported by genetic lossof-function studies, which established that dmp53 is required for transcriptional induction of rpr proteins (rpr, hid, skl) and for radiation-induced apoptosis. 3 General development was not affected in the dmp53 mutants, [19][20][21] but mild defects in longevity and fertility were found. Where studied, dmp53 does not engage damage-induced cell cycle checkpoints and, consistent with this, the Drosophila ortholog of p21 is unresponsive to irradiation.…”
Section: Drosophila Melanogastermentioning
confidence: 93%
“…Another strategy that may be promising for X. tropicalis is the homologous recombination strategy developed by Golic and collaborators for Drosophila Golic, 2000, 2001;Rong et al, 2002). In this approach, in vivo excision of an introduced targeting construct by using a rare-cutting restriction enzyme enhances homologous integration by presentation of recombinogenic DNA ends.…”
Section: Strategies For Inhibiting Particular Gene Activities and Tarmentioning
confidence: 99%